2013
DOI: 10.1061/(asce)hz.2153-5515.0000141
|View full text |Cite
|
Sign up to set email alerts
|

Game Theory–Based Multistakeholder Planning for Electronic Waste Management

Abstract: Stakeholder decision making is needed for implementing policies that affect both initial purchase decisions of electronic gadgets and ultimate decisions about land disposal/recycling or storage of electronic waste. In consumer electronics, a long-term relationship between manufacturer and consumer might lead to contracts that create incentives for consumers to return used electronic gadgets. The result could be more effective economically and environmentally for involved stakeholders like manufacturers, consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The player with maximum contribution can obtain more profit. Every participant in coalition wants maximum profit [42]. In cooperative GT, Shapley value, a solution concept is proposed in [43].…”
Section: Gt Based Price Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The player with maximum contribution can obtain more profit. Every participant in coalition wants maximum profit [42]. In cooperative GT, Shapley value, a solution concept is proposed in [43].…”
Section: Gt Based Price Modelmentioning
confidence: 99%
“…For coalition S, ν(S) describes the total expected sum of marginal distribution that a member of S can obtain. In Equation (10), numerator is equal to the number of permutations of S whereas denominator is the total number of permutation [42]. Permutation is used to find out all the possibilities in which coalition can formed, for N homes it is calculated as 2 N .…”
Section: Gt Based Price Modelmentioning
confidence: 99%
“…They simulated the results and found that implementation of such schemes could be more cost-effective and better for increasing its social acceptability. Kaushal and Nema (2013a) conducted a study on the deposit-refund system for environmentally safe handling of computer waste, and they proposed EPR-based schemes to investigate the relationships between manufacturers and consumers. An oil recovery program in western Canada is another example of a deposit-refund scheme.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The present study is motivated by the researchers’ work on the deposit-refund system that aims to develop EPR schemes for a variety of products (Cahill et al, 2010; Kaushal and Nema, 2013a; Lin and Chiu, 2015; Silveira and Chang, 2011) and these are discussed in the literature review section. These studies present the framework of EPR schemes with a wide range of models but the economic accountability of the stakeholders (SCMs) during simulation of EPR policy has not been focused upon with reference to the market scenario of a particular area.…”
Section: Introductionmentioning
confidence: 99%